The effect of the menstrual cycle on running economy - Goldsmith, E.; Glaister, M. (The Journal of Sports Medicine and Physical Fitness, 2020)
BACKGROUND: The aim of this study was to examine the effect of the menstrual cycle on running economy (RE). METHODS: Using a repeated-measures design, ten eumenorrheic, trained female runners (age: 32±6 yrs, VO2max: 59.7±4.7 mL/kg/min) completed four, weekly, identical sub-maximal and maximal incremental step tests on a treadmill to measure physiological responses across a full menstrual cycle. For phase comparison, the results from the trials that fell in the early follicular (low estrogen, low progesterone), late follicular (high estrogen, low progesterone) and mid-luteal (high estrogen, high progesterone) phases were used. RESULTS: There was a significant effect of menstrual cycle phase on RE (P=0.001), with RE in the mid-luteal (ML) phase being worse than that of the early follicular (EF) (+2.33 mL/kg·min; P=0.026) and late follicular (LF) (+2.17 mL/kg/min; P=0.011) phases. The ML phase also resulted in elevated core temperature versus the EF (+0.51 ºC; P=0.001) and LF (+0.66 ºC; P=0.037) phases, and elevated minute ventilation versus the EF phase (+3.83 L·min-1; P=0.003). No significant effects of menstrual cycle phase were found on body mass, heart rate, ratings of perceived exertion, time-to-exhaustion, maximal oxygen consumption, or blood lactate concentration. CONCLUSIONS: In the ML phase, which causes increased core temperature and minute ventilation, RE is impaired at exercise intensities that are applicable to training and performance. In physiologically stressful environments, this impairment in RE may have a significant impact on training and performance.